(untitled) (Research, Society and Development, 2024)
Objective: This research aims to report the experience of three patients undergoing ecmotherapy, describing the general prognosis and factors related to care. Methodology: this is an experience report carried out by resident nurses of the Multidisciplinary Residency Program in Intensive Care during the optional internship in a large hospital in the capital of São Paulo. During the experience, it was possible to follow three cases of patients on ECMO, all in critical health, which justified the therapy. Results: at the end of the experience, it was possible to analyze that due to advances in technological devices, it is possible to offer high-level therapy to patients hospitalized in highly complex units. The professionals in the intensive care unit, doctors, and the nursing team underwent specific training regarding the functioning of the device and the precautions that must be taken. Conclusion of the study: hospitals that offer treatment through ecmotherapy must carry out ongoing health education, which trains the team to provide health care to patients undergoing ECMO.